Necrotizing fasciitis resulting from Streptococcus pneumoniae in recently diagnosed systemic lupus erythematosus case - Isik, A.; Koca, S. S. (Springer, 2007)
Systemic lupus erythematosus (SLE) is a systemic, autoimmune disease. SLE patients are prone to infections, and their hospital admissions and mortality are most commonly associated with infections. Necrotizing fasciitis (NF) is a rare, life-threatening infection of the subcutaneous tissue. In this report, NF associated with Streptococcus pneumoniae (SPN) that developed within hours and resulted in death is presented in a 46-year-old female case who was recently diagnosed as SLE and did not receive any medication (steroid, immunosuppressive, etc.) except for etodolac. This case shows that SLE can generate predisposition to NF, and SPN can play a role in NF etiology.
Keywords: necrotizing fasciitis; Streptococcus pneumoniae; systemic lupus erythematosus